SEASONAL VARIATION OF PHYTOPLANKTON OF A WATER SYSTEM IN IRAQ - Islam, A K M Sirajul; Khalaf, A N; Al-Jaferi, A R (Indian Journal of Fisheries, 2011)
Seasonal variation of phytoplankton was studied in Rashdiyah reservoir, Baghdad, Iraq, from January to December, 1981. Phytoplankton population showed two maxima, first one in M^rch and a second one in November. The total number of phytoplankton varied between 5 x 10^/1 in March and 0.3 x 10*/l in July. Dry weight of phytoplankton also showed a similar pattern. The overwhelming majority of the speciÂ«s were diatoms followed by green and bluegreen algae. Phytoplankton was abundant in spring and autumn followed by winter and summer